2015
DOI: 10.7883/yoken.jjid.2014.051
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Pseudomonas luteola in Pediatric Patients

Abstract: SUMMARY: Pseudomonas luteola has rarely been reported as a human pathogen. The clinical manifestations of P. luteola bacteremia and its susceptibility to antibiotics have not been characterized. This retrospective study was conducted at a 382-bed tertiary care center in Turkey. During the 9-year study period, 7 patients (5 females and 2 males) were diagnosed with P. luteola bacteremia. Six of these patients had hospital-acquired bacteremia, whereas 1 patient had community-acquired P. luteola infection. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Similar combination of Pseudomonas luteola and Escherichia vulneris has been reported to cause "round pneumonia", in which the lesion has been detected on the chest radiographs as solitary lung nodule, which are first suspected to be a lung cancer [23]. Infections with Pseudomonas luteola are less common, but cases of bacteremia, empyema, endocarditis, post-surgical infections and peritonitis have been reported [24]. Enterobacter cloacae is involved in the normal intestinal microbiota in many people.…”
Section: Discussionmentioning
confidence: 86%
“…Similar combination of Pseudomonas luteola and Escherichia vulneris has been reported to cause "round pneumonia", in which the lesion has been detected on the chest radiographs as solitary lung nodule, which are first suspected to be a lung cancer [23]. Infections with Pseudomonas luteola are less common, but cases of bacteremia, empyema, endocarditis, post-surgical infections and peritonitis have been reported [24]. Enterobacter cloacae is involved in the normal intestinal microbiota in many people.…”
Section: Discussionmentioning
confidence: 86%
“…As was seen in this instance, P. luteola can be involved in infections that lead to severe morbidity, and may even result in mortality. In their retrospective study, Bayhan et al assessed the number of cases of P. luteola at a pediatric hospital [ 16 ]. They found that the majority of cases of P. luteola (85.7%, 6/7 patients) were hospital acquired and that nosocomial infection by the pathogen tended to present as bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas luteola (formerly Chryseomonas luteola) is a catalase positive, oxidase negative, motile Gram negative bacillus of the family Pseudomonaceae. 2 While P. luteola infections are less common than those of P. aeruginosa, there have been case reports of the bacterium causing bacteremia, empyema, prosthetic valve endocarditis, post-surgical infections, and peritonitis. [3][4][5][6] Although most often found in the soil and water sources, P. luteola has been isolated in animals, including turtles, tortoises and fish.…”
Section: Discussionmentioning
confidence: 99%